The Role of Commercial Feed Additive (Maxi-Yeast®) in Broilers Challenged with Campylobacter Jejuni on Weight Gain, Feed Consumption, Feed Conversion Ratio - Wahyuni, Agnes E. T. H.; Tae, Agustina Viktoria (Journal of Tropical Animal Science and Technology, 2025)
Antibiotic growth promoters (AGPs) are commonly used by the public to increase chicken growth, but they have health risks, namely causing resistance in humans and animals. Therefore, experts have begun to seek substitutes that focus on natural ingredients, such as yeast, as non-antibiotic alternatives. The most commonly used yeast probiotic is Saccharomyces cerevisiae (S._cerevisiae) var. Boulardi. One of the pathogenic microorganisms that attacks poultry is Campylobacter jejuni. This study aims to determine the effect of feed additives (S._cerevisiae), in broiler chickens on performance (weight gain, feed consumption, feed conversion ratio (FCR)) after being infected with C. jejuni. A total of 36-day-old chicks (DOC) were grouped into 3 based on feed provision, namely, commercial feed group (I), commercial feed group + AGP (II), and commercial feed group + Feed additives (S._cerevisiae) (III). The three groups were further divided into 2 treatments, namely (A) without challenge test (control) and (B) challenge test. Feed mixing was done manually, drinking was given ad libitum and vaccination was according to the field program. Weighing of body weight and remaining feed was done every week. A challenge test with C. jejuni was done on the 21st day with a concentration of 1x109 CFU/mL. The results obtained for overall weight gain in weeks 1 to 3 of each feed group, statistically did not show a significant difference (P>0.05), although the numbers showed a difference. Weeks 4 and 5 of the control group's weight gain statistically showed a significant difference between groups (P<0.05). The challenge test group, week 4 experienced a decrease in weight gain and was not statistically significantly different (P>0.05) but in week 5 there was an increase in weight and was statistically significantly different (P<0.05). Conclusion: Providing commercial feed additives (S. cerevisiae) can increase weight gain, and reduce feed consumption and FCR.